Fresamento de topo em compósito de fibra do caule da bananeira e poliuretano derivado do óleo de mamona - Ellenberger, Alessandro (2018)
The production of goods that use inputs from planted forests, such as reconstituted wood panels used by the furniture industry, has been questioned by consumers and researchers due to environmental issues involved in the manufacturing process, such as the use of polymers of petroleum origin and the use of formaldehyde in the binder. In this scenario, materials are being developed that use raw materials from renewable sources and from waste discarded by agricultural and industrial processes. A proposed solution is the composite with natural fibers, using polyurethane derived from castor oil as a binder. For commercial use it is necessary to know the possibilities of machining through existing systems. The objective of this work is to analyze the process of end milling in a fiber composite of banana stem agglutinated with polyurethane derived from castor oil, evaluating surface roughness, surface defects and machining forces. The study was performed by milling slots in composite slabs using a carbide end mill. Higher cutting speeds proved to be better for surface roughness and generate less machining forces. The defects were concentrated in the upper edge of the channel and were influenced by the axial force of the cutter, where higher cutting speeds increased their quantity. The present work will contribute to the adequacy of the milling process in composite materials with natural fibers, stimulating the commercial use of the same.